Quality of Narcotics Prevention, Eradication, Abuse, and Illicit Circulation Services (P4GN) at BNN Gorontalo Province in Drug Addict Rehabilitation Patients - Tessy Nursanty Podungge; Asna Aneta; Rusli Isa (Cita konsultindo, 2025)
Tessy Nursanty Podungge. NIM 711524024.